2020
DOI: 10.1093/ntr/ntaa092
|View full text |Cite
|
Sign up to set email alerts
|

Compliance With FDA Nicotine Warning Statement Provisions in E-liquid Promotion Posts on Instagram

Abstract: Introduction Effective August 2018, the U.S. Food and Drug Administration required that nicotine addiction warnings be placed on ads for nicotine containing e-liquids. As per FDA comments, this provision pertains to visual ads communicated via social media, raising questions about compliance within the large e-liquid promotion community on Instagram. Methods This study examines use of warnings on promotional Instagram posts b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…It is not possible to say with absolute certainty that all posts made by influencers were truly sponsored, since some influencers may also upload content that they were not incentivised to post about. This may overstate the number of sponsored posts, as well as complicate enforcement efforts 47…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to say with absolute certainty that all posts made by influencers were truly sponsored, since some influencers may also upload content that they were not incentivised to post about. This may overstate the number of sponsored posts, as well as complicate enforcement efforts 47…”
Section: Discussionmentioning
confidence: 99%
“…This may overstate the number of sponsored posts, as well as complicate enforcement efforts. 47 We only conducted a descriptive analysis and looked at the most frequently used measure in social network analysis, degree centrality. We did not assess the effect of exposure to promotional content on followers or product users.…”
Section: Limitationsmentioning
confidence: 99%
“…Helvetica or Arial bold) font size (The U.S. Food and Drug Administration 2020). Several studies (Vassey et al 2020;Laestadius et al 2020) evaluated compliance with the 2018 FDA requirements for warning labels on Instagram. Vassey et al (2020) manually reviewed 2,000 images posted in 2019 and found that only 7% included FDA-mandated warning statements.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the international posts featured vaping products distributed in the U.S. and would therefore still be subject to compliance with the FDA warning-label regulations (Vassey et al 2020). Laestadius et al (2020) manually reviewed 1,000 posts collected in late 2018-early 2020 and found that only 13% included warning statements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation